The identity of Megachile dorsalis Pérez and Megachile burdigalensis Benoist, sp. rev. (Hymenoptera: Apoidea: Megachilidae) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 1998)
Based on the examination of the type material of Megachile dorsalis Pérez 1879 and field observations, Megachile burdigalensis Benoist 1940 is recognized as a distinct species and its lectotype is designated. A till now unknown female of this species is described and compared with its closest relative, Megachile flabellipes Pérez 1895. M. burdigalensis collects pollen from Lotus tenuis (Fabaceae). A redecription of a Megachile dorsalis female is given.
Keywords: entomologija; kožokrilci; zoologija; zoology